Pengaruh Perceived Price dan Perceived Usefulness terhadap Keputusan Pembelian pada Pengguna Aplikasi Layanan Spotify Premium di Kota Surabaya - Amirah, Anandah; Wardhani, Nuruni Ika Kusuma (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to find out the influence of price perceived and usefulness perceived on purchase decision on users of premium Spotify applications in Surabaya City. This study used questionnaires to obtain data for quantitative research. The number of samples obtained in accordance with Ghozali's formula was 96 respondents. Sampling techniques use a non-probability sampling technique that is purposive sampling. The data analysis method in this study used SEM-PLS 3.0 with validity, reliability, and hypothesis test. The research results show that (1) price perceived contributes to purchase decisions on users of the premium spotify application in Surabaya City. (2) usefulness perceived contributes to purchase decisions on users of premium spotify applications in Surabaya City.